The Role of Teachers in Enhancing Religious Moderation through Problem Based Multicultural Education - Selvia Ruyatus Saefullah; Erni Furwanti; Sunsun Pradana Yogaswara; Neni Utami Adiningsih; Reni Marlina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Indonesia’s multicultural society presents significant challenges and opportunities for strengthening religious moderation within educational environments. Increasing cases of intolerance, social polarization, and interreligious conflict indicate the urgent need for inclusive and diversity-responsive educational approaches. This study aims to analyze the role of teachers in enhancing religious moderation through Problem-Based Multicultural Education. The research employed a qualitative approach using a Systematic Literature Review (SLR) design. Data were collected from peer-reviewed articles indexed in Scopus, Google Scholar, ScienceDirect, and other academic databases published between 2019 and 2026. The review process followed identification, screening, eligibility, thematic analysis, and synthesis stages based on PRISMA guidelines. A total of 48 relevant studies were selected and analyzed comprehensively. The findings revealed that 91% of the reviewed studies emphasized teachers’ strategic roles in fostering tolerance, inclusiveness, empathy, and democratic values within multicultural classrooms. Approximately 87% of the studies also demonstrated that Problem-Based Multicultural Education effectively improves students’ critical thinking, collaborative learning, and peaceful coexistence in diverse social contexts. The study further identified that contextual learning activities based on real social problems significantly contribute to strengthening religious moderation and reducing discriminatory attitudes among students. The study concludes that integrating teachers’ pedagogical competence, multicultural awareness, and problem-based learning provides an effective educational framework for developing harmonious and inclusive learning environments in pluralistic societies.